Intracellular calcium signals display an avalanche-like behavior over multiple lengthscales - Lopez, Lucía; Piegari, Estefanía; Sigaut, Lorena; Ponce Dawson, Silvina (Frontiers in Physiology, 2012)
Many natural phenomena display "self-organized criticality'' (SOC). This refers to spatially extended systems for which patterns of activity characterized by different lengthscales can occur with a probability density that follows a power law with pattern size. Differently from power laws at phase transitions, systems displaying SOC do not need the tuning of an external parameter. Here we analyze intracellular calcium Ca2+ signals, a key component of the signaling toolkit of almost any cell type. Ca2+ signals can either be spatially restricted (local) or propagate throughout the cell (global). Different models have suggested that the transition from local to global signals is similar to that of directed percolation. Directed percolation has been associated, in turn, to the appearance of self-organized criticality. In this paper we discuss these issues within the framework of simple models of Ca2+ signal propagation. We also analyze the size distribution of local signals ("puffs'') observed in immature Xenopus Laevis oocytes. The puff amplitude distribution obtained from observed local signals is not Gaussian with a noticeable fraction of large size events. The experimental distribution of puff areas in the spatio-temporal record of the image has a long tail that is approximately log-normal. The distribution can also be fitted with a power law relationship albeit with a smaller goodness of fit. The power law behavior is encountered within a simple model that includes some coupling among individual signals for a wide range of parameter values. An analysis of the model shows that a global elevation of the Ca2+ concentration plays a major role in determining whether the puff size distribution is long-tailed or not. This suggests that Ca2+-clearing from the cytosol is key to determine whether IP3-mediated Ca2+ signals can display a SOC-like behavior or not.